Association of stature and mental problems among adolescents in Jatinangor District, West Java (Faculty of Medicine Universitas Indonesia, 2018)
Background: The prevalence of short stature during adolescence in Indonesia remains high. Adolescents are very concerned about their stature. Most adolescent health problems are related to psychosocial issues. The prevalence of mental disorders among adolescents in Indonesia is 6.0%, and West Java is 9.3%. The aim of this study was to analyze the association between stature and mental problems during middle adolescence.Methods: This analytical cross-sectional study was performed at three high schools in Jatinangor, West Java, Indonesia. The subjects were students, age of 16-17 years old without physical abnormalities other than short stature and weight problems. Mental problems were screened using a self-report Strength and Difficulties Questionnaire (SDQ). Data were analyzed using the chi-square test with prevalence risk.Results: Of the 150 respondents, 116 subjects met the inclusion and exclusion criteria. The prevalence of short stature was 55 cases (47.4%) and more predominant in females. Among the behavioral and emotional problems assessed, the emotional symptom was associated significantly with short stature; prevalence ratio 1.87 (95% CI=1.14; 3.08). There was no significant association of short stature with other attributes such as conduct, hyperactivity, peer problems, and total difficulties (p>0.05).Conclusion: Stature in adolescence is associated with emotional problems.